As cirúrgias espirituais como prática terapêutica: estudo de caso - Couras, Raimunda Neves de Almeida (2009)
The spiritual cures have been used by mankind since the most remote antiquity, in all eras and by all peoples. The spiritual surgeries occur under the claim that there is intervention of Spirits, with medical knowledge, as regard both the patient s biological and energetic organization. According to explanations given by the spiritual physicians the intervention occurs in what is called the spiritual body that, as a result, reorganizes the biological body. This dissertation aimed to investigate the surgeries, their consequences concerning health and the experiences lived by people who were assisted at União Espírita Diogo de Vasconcelos, in João Pessoa, Paraiba. The research analyzed three cases of people, presenting different pathologies, who were subjected to spiritual surgeries whose clinical histories were documented by means of complementary exams. The study involved a set of sequential procedures, having as starting point the project s elaboration, then the ethical processes, thirdly the meetings in order to inform about the subject and, finally, by defining the research s collaborators. After such phases, the interviews were accomplished, the recorded material was, then, transcribed, textualized, transcreated and identified the vital tone for each of the speeches. The thematic oral history was the chosen method for analysis of the recorded interviews with the collaborators and the medium who, once in a medianimic action, rendered voice to the spiritual physician. The results show a noteworthy improvement, originated from the spiritual treatment process in which the collaborators are impelled to change their habits and behavior, and this reflected on a global betterment of their health.